La complejidad del régimen internacional y la gobernanza regional: evidencia de Latinoamérica - Gómez-Mera, Laura (El Colegio de México A.C., 2015)
The proliferation of overlapping agreements and organizations, and the resulting density in international regimes, lead to increasing attention to the consequences of growing regime complexity on the politics and the effectiveness of global governance. This paper analyzes if the increasing density of economic regimes in the region worked strengthen or undermine the effectiveness of collaboration efforts. I discuss empirical evidence suggesting the presence and relevance of some of these mechanisms in the Americas. It is observed that competitive dynamics among states and regimes with divergent visions and objectives undermines regional cohesion and solidarity.